Examining the nonkin support networks of orphaned adolescents participating in a family‐based economic‐strengthening intervention in Uganda. Issue 3 (5th November 2018) - Nabunya, Proscovia; Padgett, Deborah; Ssewamala, Fred M.; Courtney, Mark E.; Neilands, Torsten
Abstract: In this study, we examined the nonkin support networks of orphaned adolescents participating in a family‐based economic‐strengthening intervention in HIV‐impacted communities in Uganda. We analyzed data from a cluster randomized experimental study for orphaned adolescents aged 11–17 years. Participants were randomly assigned to either the control condition, which received bolstered standard of care (BSOC) services, or the treatment condition, which received BSOC services plus an economic‐strengthening intervention. We conducted binary logistic regression analyses to examine the effect of the intervention on participants' nonkin support networks. Results indicated that the existing social support networks for orphaned adolescents are small, limited, and usually comprised individuals with similar socioeconomic situations and challenges. Because orphaned adolescents are socially isolated and the threshold for nonkin supportive services is very low, the BSOC services provided to the control condition appeared to be instrumental in their survival and well‐being. Availability of personal savings was associated with higher odds of identifying at least one supportive nonkin tie. The extended family system is still the primary and major source of social support to orphaned children in HIV‐affected communities. In the absence of public safety nets, building social assets, over and above offering economic opportunities to extended families supporting orphaned children, is critical.